(untitled) (Fiep Bulletin - online, 2011)
This study intends to understand how management models of social sports clubs are regarding spaces designated for sport as leisure. In addition, through this study it is aimed to clarify the adaptation to social sports clubs environment, to understand the management in these clubs and to identify the main strategies of social sports clubs. As methodological assumption it has adopted a qualitative descriptive bias, having as locus spaces designated for sport as leisure in social sports clubs from the city of Novo Hamburgo /RS. For information detection, semi-structured interviews were used with the actors responsible for the managements in those spaces and in loco observation of the functioning and utilization of the sports spaces in clubs. In order to obtain the results, it was used the technique of contents analysis in information gathered. The study found as main results that clubs try to adapt to continuous needs and new contexts, their practice of management range from the humanistic perspective to the integrative one and, strategies are similar to the descriptive school.